Application of fuzzy dematel method to analyse s-CO2 Brayton power systems - Bashan, Veysi; Ust, Yasin (IOS PRESS, 2019)
Supercritical carbon dioxide (s-CO2) Brayton power cycle has increasingly attracted attention due to having greater efficiency than conventional power cycles. Thus, s-CO2 systems have begun being tested all around the world, first at the laboratory scale, then as actual medium-capacity systems for ships' main engines, and finally as large terrestrial power systems. In order to understand system performance during these tests, one must know the causes and effects of the operating regime of the system and its failures. In this context, the study analyzes 15 fundamental problems of power system-related components using the fuzzy Decision-Making Trial and Evaluation Laboratory (DEMATEL) method. The DEMATEL method allows for identifying and analyzing important errors and/or problems in the s-CO2 Brayton cycle according to the cause-and-effect relationship scheme Similarly, fuzzy sets are freed from uncertainty in decision-making and from the verbal comments of experts in DEMATEL. When examining the results, fire protection and/or firefighting problems, generator problems, gearbox problems, and radiator problems appear to have high importance in terms of causes. In addition, turbine problems, electrical problems, catalytic combustion-chamber problems, instrumentation, and control-system problems are also important in terms of effects. The study's obtained results will strongly contribute to the operational safety and prevention of serious high-speed, high-temperature, and high-pressure machinery effects for laboratory-scale, medium-capacity, and actual-terrestrial s-CO2 power systems.
Keywords: Super critic; carbon dioxide; Brayton; fuzzy DEMATEL; faults; CRITICAL OPERATIONAL FAULTS; TURBINE BLADE FAILURE; MANAGEMENT; EVALUATE; ANP; ENERGY; TOPSIS; SELECTION; RISK; AHP; Computer Science